Gender Tendency Towards Using Taboo Words Among University Students - Mohammadi, Mohammad Javad; Eini Roumiani, Milad; Hekmatshoar Tabari, Bizhan (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
There are many factors which affect the language using and language choosing in every society. One of these factors is the controversial factor of gender and its effect on language using and the elements of language used in community and society. To expand the scope of gender-bound language, the current study intends to investigate the use of taboo words among the university students by both genders. To this aim, 40 students, 20 males and 20 females were selected to be compared using a researcher made 15 items questionnaire questioning the participants about using taboo words in specific situations. The results reveal that using taboo words by two groups is not of significant difference except in some situations.